Clinical Evaluation of Various Cardiac Parameters with Emphasis on Doppler Echocardiography in Healthy Labrador Retriever Dogs - P Nanda, Parth; M Parmar, Saurabh; J Kunjadiya, Rajan; A Vala, Jignesh; D Patel, Manish; A Mehta, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Looking to the importance of emerging field of cardiac diseases in pet dogs, the present study was aimed to establish reference ranges  for cardiac parameters and evaluate the impact of body weight in clinically healthy Labrador retrievers. During the study, 16 adult  dogs (2-6 years) were divided into two groups based on body weight: Group I (30 kg). Diagnostic assessments  including radiography and echocardiography were performed. Radiographic evaluations revealed vertebral heart scores (VHS) of 10.48  ± 0.21 and 10.18 ± 0.19 in Group I and II with no signs of cardiac enlargement. Echocardiography showed significant weight-related  differences, with Group II exhibiting larger aortic and left atrial diameters, higher LA/Ao ratio and increased ventricular dimensions and  wall thickness. Ejection fraction (EF) was higher in Group II (73.70 ± 1.81%) than Group I (58.89 ± 2.29%), while fractional shortening (FS)  showed non-significant difference. End-diastolic (EDV) and end-systolic volumes (ESV) were significantly greater in Group II but remained  within normal range. Doppler analysis showed non-significant differences in mitral, tricuspid, aortic, or pulmonic flow velocities. Based  on results, it was concluded that body weight significantly influences cardiac parameters in Labrador retrievers underscoring the need  for weight-adjusted reference ranges. The study highlights the utility of Doppler echocardiography and radiography for precise breed  specific cardiac evaluation.
Keywords: Doppler echocardiography; Healthy Labrador Retriever; Radiography